Plan de negocios para la creación de una empresa de venta y/o arriendo de software de facturas electrónicas en la ciudad de Quito - Morán Garnica, Mónica Elizabeth (2012)
This research provides knowledge to establish a business plan that allows to implement a company to address the potential needs of entrepreneurs in the areas of electronic invoicing. Furthermore, this project will serve as a support to achieve gain greater market share, increase profitability and contribute to the generation of foreign exchange in the economy in an orderly manner and in compliance with regulations in the country.